2002
DOI: 10.1002/bip.10154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipids on elastin's viscoelastic properties

Abstract: Sodium dodecyl sulfate (SDS) was used as a model lipid to identify the molecular basis of possible lipid-induced changes in the viscoelastic behavior of arterial elastin. The chemical composition of the elastin network and the interfibrillar space was calculated from the chemical content of the elastin sample and its swelling behavior. Viscoelastic behavior was measured in aqueous SDS and in SDS plus 1 M sucrose, a deswelling agent. Viscoelastic behavior was also measured in sucrose and potassium thiocyanate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…Sample 3 is shown as a function of SDS content in Figure 4a and b. The behavior at the low concentration indicates that the interaction of SDS with elastin at low SDS levels is complex, and this is dealt with in another paper, 12 but the behavior at higher concentrations indicates a simple swelling regime that can be analyzed to identify the swelling dimensionality of the network.…”
Section: Network Swellingmentioning
confidence: 98%
See 1 more Smart Citation
“…Sample 3 is shown as a function of SDS content in Figure 4a and b. The behavior at the low concentration indicates that the interaction of SDS with elastin at low SDS levels is complex, and this is dealt with in another paper, 12 but the behavior at higher concentrations indicates a simple swelling regime that can be analyzed to identify the swelling dimensionality of the network.…”
Section: Network Swellingmentioning
confidence: 98%
“…Elastin swelling studies in SDS support this prediction. Doubling the SDS concentration from 10 to 20 mM results in only a modest increase in swelling, from 1.26 to 1.29, 12 which would increase to only 81°. Therefore, like the one-dimension model, there is a quantitative match between the reorientation model and the data.…”
Section: Figurementioning
confidence: 98%
“…7 Several thermodynamic studies of elastin have indicated a strong dependence of the Young's modulus with the type of solvent and extent of hydration reinforcing the vital role of an aqueous environment that imparts its elasticity. [8][9][10] The strain dependence of the entropy and energy components of the stress for elastin samples in swelling equilibrium with different diluents has also been investigated. 11 It was shown that in water, the energetic component contributed $15% of the total stress.…”
mentioning
confidence: 99%
“…Elastin is a structural protein that helps to maintain the morphology of connective tissues [47][48][49]. At low temperatures, elastin is soluble in aqueous solutions.…”
Section: α-Elastin Characterizationmentioning
confidence: 99%